As maçãs do Éden e a criação de uma novela literária - Bortulini, Gabriel Eduardo (2021)
Creative Writing is still recent as an academic area in Brazil. Although its matrix is literature, literary studies seem to be not enough for the discipline, which generates theoretical knowledge, but also seeks to create new artistic works. In addition to being a little explored field, it requires interdisciplinarity, indispensable for the growth of Creative Writing within the academy, which often generates obstacles for students and teachers. Understanding the problems of writing is understanding what we write about. This thesis seeks to recreate the spaces and landscapes that are crucial for the construction of a novel. Based on some knowledge that goes beyond narrative techniques, we seek to understand the narrative space from its other systems: from the anguish of a place and its collapsing identities, where climate and vegetation are as important as language; where expectations and obsessions are the creative engine itself; where narratives approach the landscape: always a perspective in suspension, eternally unfinished, like the most perfect bonsai tree.